Audit committee characteristics and earnings quality: The role of audit quality and corporate life cycle - Muslim, Resti Yulistia; Minovia, Arie Frinola; Alhaq, Safna Falsafia; Hamdi, Mukhlizul (Journal of Accounting and Investment, 2025)
Research aims: This study investigates the influence of audit committee characteristics (size, expertise, and gender diversity) on earnings quality with audit quality as a moderating factor across various stages of the corporate life cycle. Based on life cycle theory, this study posits that each corporate life cycle stage presents different results.Design/Methodology/Approach: A purposive sampling method was employed, resulting in 395 observations from infrastructure, property, and real estate from 2018 to 2022. The classification of the corporate life cycle relies on Dickinson's (2011) model, resulting in 66, 78, 153, and 98 observations for the introduction, growth, maturity, and decline stages.Research findings: The findings reveal that audit committee expertise and gender positively affect discretionary accruals for the full sample. Audit committee size positively affects discretionary accruals in mature firms, while gender enhances discretionary accruals in both growth and mature firms. Audit quality can moderate the relationship between audit committee expertise and earnings quality in the full sample and growth firms, and also moderate the effect of gender on earnings quality in the full sample, growth, and mature firms.Theoretical contribution/ Originality: This study expands the earnings quality literature by integrating corporate life cycle theory into analyzing the dynamic role of audit committees and audit quality.Practitioner/Policy implication: The results highlight the importance of the corporate life cycle in optimizing the audit committee to enhance earnings quality.Research Limitations/Implications: This research employs a dummy variable for gender due to the limited representation of women on audit committees and limited observations at several life cycle stages.